Assess and Evaluation the Quality Of Life (Qol) Among Cancer Patients Undergoing Treatment by Using EORTC QLQ-30 Scale - Anil Kumar Agarwal; Abhishek Yadav; Chanderpal Singh Yadav; Ramniwas Mahore; Prashant Dixit (Medsci Publications, 2022)
Background: Cancer is a challenge for majority of population's health-related quality of life (HRQoL), compromising their physical health and emotional well-being. QoL is equally distributed among different social groups. The aim of this study to analyze the impact of clinical characteristics and social determinants of health on the QoL of a cohort of persons diagnosed and/or treated for cancer. Methods: We performed a cross-sectional study in a cohort of 155 with various stages of cancer at different stages of their disease. Data were obtained using questionnaires QLQ-C30 from the European Organization for Research and Treatment of Cancer (EORTC), which include a set of functional and symptomatic scales. We conducted descriptive and bivariate analysis using the Chi-Square test, Anova Test and adjusted for relevant variables using logistic regression. The dependent variables were the functional scales of QoL and the independent variables were socio-demographic and clinical variables. Results: Among the participants, 80(51.6%) were male and 75(48.4%) were female and majority 66(42.6%) in between the age of 40-60 years. Large proportion of patients were diagnosed with Oral cancer 67(43.2%), and Breast cancer 23(14.8%), and the clinical stages during the beginning of therapy were maximum at stage II a 104(67.1%). The mean of global health status/QoL was 52.34 (SD= 23.34). Quality of life was found to be significantly associated with some functional scales as role functioning (P≤0.001), social function, (P=0.00), and symptom scales as pain (P=0.00), loss of appetite (P=0.004) and financial impact (P=0.02) as well as associations were noted in relation to socio demographic characteristics. Women from the most disadvantaged class, and showed the poorest results for most of the function scales. In contrast, age, education, occupation and social status had differential effects depending on the function studied. The highest functional status was cognitive functioning (54.58±27.68). Conclusions: The cancer diagnosis has become more prevalent and carries significant changes to the method of living with physical and emotional changes in term of quality of life (QoL) because of inconvenience, torment, disfigurement, reliance and loss of confidence. In addition, addressing the unmet needs of these patients and ensuring higher satisfaction rate are recommended to maintain adequate HRQoL.